If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2y + 3 = 9 + 6y Reorder the terms: 3 + 2y = 9 + 6y Solving 3 + 2y = 9 + 6y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-6y' to each side of the equation. 3 + 2y + -6y = 9 + 6y + -6y Combine like terms: 2y + -6y = -4y 3 + -4y = 9 + 6y + -6y Combine like terms: 6y + -6y = 0 3 + -4y = 9 + 0 3 + -4y = 9 Add '-3' to each side of the equation. 3 + -3 + -4y = 9 + -3 Combine like terms: 3 + -3 = 0 0 + -4y = 9 + -3 -4y = 9 + -3 Combine like terms: 9 + -3 = 6 -4y = 6 Divide each side by '-4'. y = -1.5 Simplifying y = -1.5
| 15x^2+5-[5(x^2-7)+9]= | | 5p^2=300+20p | | 2x-1+2x=4x+28 | | -6=-5 | | -31+6x=-1-3(-5x+1) | | 4k^3w+20k^2w^2+25kw^3=0 | | 4(6x^2-7)-[6(3x^2-4)+3]= | | 5n+3(n+a)=28 | | lx(x+8)+ln(x-1)=2lnx | | 7-2(4r+3)=-6 | | 3(4-x)=10+2x | | 2w^2-4w-70=0 | | 67-b=49 | | 4(7-2n)+4n=-5n+34 | | A=650-8(75) | | -3z^2+2z-35=0 | | y=0.5+4 | | -8c=24 | | 3ax(7xa)= | | 0.04(x^3+125)+2=14-x | | 7(x+4)=7 | | (4x-16)(4x-16)-(x-2)(x-2)=(8-x)(8-x) | | 16x+27=15x+19 | | -q=6 | | -8+2=26 | | 5x^2-21x=18 | | 7x+2=6x-2 | | 12m^2-8m+3=0 | | 4(8k+4)-1=-3k+15 | | (2x+5)(x-3)=30 | | 0.6x^2=3.6+0.6 | | 3x^3-7x-10=0 |